Business model : reducing waiting time for patients through a self-check-in and a waiting time prediction tool for german medical practices - Vecchio, Alexander Schulz Del (2022)
The aim of this thesis is to develop an initial business model and validate the business idea of the start-up, named DOC+. The solution offers the most time efficient way to plan and execute a physician visit for practices and patients though self-check-in and though waiting time predictions. First, the business idea is described, followed by an analytical and structured approach to create the business model. It is validated through the analysis of an online survey for patients and semi-structured interviews with physicians. The quantitative data is statistically analyzed with regression analyses and the qualitative data according to Mayring's coding scheme. Ash Maurya's Lean Canvas, a one-page business model, serves as the basis for the thesis. It is designed to serve as a foundation for DOC+ and for the evaluation of strategic plans and projects, which will be refined in future iteration steps. To fill in the key frames of the canvas, different frameworks are used. Key findings are that physicians have a demand to address root causes that trigger waiting times. This points at the excessive burden of administrative tasks and the need for relief. This also represents the greatest value creation for the paying customer, the physician: Reduction of workload for staff and their use of time for essential tasks. It is also identified that it is more advantageous for DOC+ to collaborate than to compete. The biggest advantage for collaboration with a competitor is the reduction of market entry barriers and having access to their resources.